How do we improve nurse preparedness on pandemic: Learning from Theory of Planned Behavior - Lisnawati, Luh Gede (Public Health and Preventive Medicine Archive, 2024)
Background and purpose: The drastic elevation in the number of patients during the COVID-19 pandemic demands the preparedness of nurses to provide quality services to COVID-19 patients. The purpose of this study was to determine the relationship between knowledge, attitudes, self-esteem, and nurses' intentions towards preparedness in facing the COVID-19 pandemic and an overview of the factors that influence it. Methods: This study used a quantitative method with a cross-sectional analytic design, conducted at Sanglah General Hospital in Bali Province, Indonesia and involved 333 nurses with a total sampling technique. The research data was collected with a google form related to demographic characteristics (age, gender, education level, and length of work), knowledge, attitudes, self-esteem, intentions, and nurse preparedness. Furthermore, data were analyzed using descriptive statistics and Chi-Square tests (α<0.05). Results: Most of the respondents were female (85.6%), had an associate degree Diploma III education history (75.7%), had the longest working time of 34 years, and the oldest age was 57 years. This study found that most nurses had poor preparedness (53.8%), good knowledge (65.5%), good attitude (51.7%), high self-esteem (68.2%), and good intentions (86.5%). The correlation test showed a significant relationship between gender (p=0.033), attitude (p<0.001), self-esteem (p<0.001), and intention (p<0.001) on preparedness for the COVID-19 outbreak. Meanwhile, knowledge (p=0.784), ages (p=0.120), education levels (p=0.094), and length of work (p=0.100) were not related significantly to nurses' preparedness for the COVID-19 pandemic. Conclusion: Nurses’ readiness is related to attitude, self-esteem, intention, and gender. In improving nurses' preparedness in carrying out disease management during a pandemic, efforts are needed to improve attitudes, self-esteem, and intentions. These efforts can be part of the hospital disaster plan program by providing psychosocial support to improve attitudes, self-esteem, and intentions.